병원행정직 종사자중 전공분야별 직무만족과 조직몰입 - 황병덕(Byung-Deog Hwang) (한국콘텐츠학회 논문지, 8(6), 2008)
The purpose of this study is to analyze the level of job satisfaction and organizational commitment of administrative staffs in hospitals. The data for this study were collected through a self-administered survey with a structured questionnaire for 338 persons from administrative staffs working in hospitals in Ulsan and Busan Metropolitan cities. The job satisfaction(factors such as wage, performance, duty, promotion and personal relations) and organizational commitment were scored from 5(very satisfied) to 1(very unsatisfied). The collected data from the survey were analyzed by frequency, ANOVA, correlation analysis and multiple regression analysis. The results are as follows: Medical technicians, health administrators, nurses and the others were ranked in order in the job satisfaction. Medical technicians, nurses, health administrators, and the others were ranked in order in the organizational commitment. The correlation analysis showed that the job satisfaction and the organizational commitment had positive correlation in the factors of wage, performance duty, promotion and personal relations. 본 연구는 병원행정직 종사자의 직무만족과 조직몰입도를 파악하고자 울산과 부산지역의 의료기관 행정직원에게 설문조사를 한 결과 338명이 연구대상자로 선정되었다. 직무만족과(임금요인, 담당직무, 승진, 대인관계요인) 조직몰입은 Like리 5점 척도로 5점(매우 그렇다)부터 1점(매우 그렇지 않다)으로 구성되었다. 자료 분석은 빈도분석, 분산분석(ANOVA), 상관관계와 다중회귀분석을 실시하였다. 그 결과는 다음과 같다. 직무만족도는 의료기사전공, 보건(원무)행정전공, 간호사전공 그리고 고졸 및 기타 전공 순으로 높았다. 조직몰입도는 의료기사전공, 간호사전공, 보건(원무)행정전공, 그리고 고졸 및 기타 전공 순으로 높았다. 직무만족과 조직몰입 변수간의 상관관계는 임금, 담당직무, 승진, 대인, 조직몰입도 모두 뚜렷한 정의 관계로 나타났다.